Effects of regional location on the genotype and phenotype of historical Irish brewing yeast - Kerruish, Daniel W. M.; Cormican, Paul; Kenny, Elaine M.; Whelan, Carl J. M.; Gilsenan, Steve; Colgan, Eibhlin; Smart, Katherine A.; Boulton, Chris A.; Stelma, Sandra N. E. (Frontiers in Microbiology, 2025)
Most commercial beers are made using water, malted barley, and hops as the principal ingredients and Saccharomyces yeast as the transforming microorganism. The yeast is used in a semi-conservative process in which crops are collected from one fermentation, stored, and a proportion recycled into a subsequent fermentation. This process differs from wine, cider, and spirit manufacturing where the yeast culture is only used once. The serial fermentation process is continued approximately 8–12 times after which a new culture of verified purity and identity is introduced. This increases the likelihood that the yeast remains true to type. Many commercial brewers use proprietary strains the origins of which are usually unknown. Advances in genetic analyses provide a means for probing the origins of brewing yeast strains, and in this study, six historical Irish brewing yeasts from five breweries located within Ireland were assessed. Using Illumina sequencing technology, whole-genome sequencing data were generated. Single nucleotide polymorphism analysis of these data established that the historical Irish brewing yeast group falls within the previously described “Britain” subpopulation Beer 1 clade. Further analysis established that the six historical Irish brewing yeasts separate into two subgroupings, which associated with specific regional locations. Furthermore, the assessment of the six historical Irish brewing yeast phenotypic attributes relevant to brewing correlated within the same regional location groupings. Our data provide further evidence of how brewing requirements associated with specific beer styles have influenced yeast strain selection.